PENGEMBANGAN SENYAWA TURUNAN BENZALASETON SEBAGAI SENYAWA TABIR SURYA - Prabawati, Susy Yunita; Wijayanto, A; Wirahadi, Aria (Universitas Ahmad Dahlan, 2014)
The goal of this research was to synthesize benzalaceton derivative i.e. 4-dimethyl-aminodibenzalacetonto increase the potency as sunscreen agent. The synthesis was carried out through aldolcondensation reaction with 4- dimetilamino-benzaldehida as a starting material and NaOH as catalystat various reaction times i.e. 3 , 4 and 6 hours. The characterizations of the product was observed bymelting point, FTIR and 1H NMR spectrometers. The product was obtained as a yellowish orangesolid with a melting point between 62-640C. The activity assay as sunscreen agent showed that the 4 âdimethylamino-dibenzalaseton have a maximum wavelength at 340 nm, so its can be active as asunscreen in the UV - A rays. The SPF value at 15 ppm was 17.409 with ultra protection type.